Effectiveness Analysis of Indonesia's Port State Control Inspection Under Tokyo MOU: A Mixed-Methods Approach - Schouten, Femmy Sofie; Wanadi, M. Adil; Kusuma, Wisnu Wardana; Pramono, Agus; Prakosa, Dandun; Laksamana, Rio (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STIP Jakarta, 2025)
Port State Control (PSC) represents a critical mechanism for ensuring maritime safety, environmental protection, and compliance with international shipping regulations. As a member of the Tokyo Memorandum of Understanding (Tokyo MOU), Indonesia conducts PSC inspections to monitor foreign vessels operating within its territorial waters. This study examines the effectiveness of Indonesia's PSC inspections under the Tokyo MOU framework through comprehensive analysis of ship detention trends, common deficiencies, and regulatory enforcement challenges. A mixed-methods research approach is employed, combining quantitative analysis of PSC inspection and detention data from 2018-2022 with qualitative assessments of inspection procedures and regulatory frameworks. Findings indicate that while Indonesia has demonstrated improvement in PSC implementation, significant challenges persist in inspection consistency, resource allocation, and systematic coverage. The study reveals that Indonesia conducts an average of 1,542 annual inspections with a detention rate of 5.2%, yet inspection coverage remains at 35-40% of total foreign vessel arrivals, below the regional average of 70%. The research highlights the critical need for enhanced coordination among maritime authorities, comprehensive inspector training programs, and stricter regulatory compliance mechanisms to optimize inspection effectiveness. The study concludes that implementing a more rigorous and consistent PSC approach will contribute significantly to safer maritime operations and reduced environmental risks. This research contributes to maritime safety literature by providing empirical insights into PSC implementation challenges in developing maritime nations, accompanied by evidence-based policy recommendations to strengthen regulatory practices and advance global maritime safety standards.